The association between time preference and net worth: incentivized choice and scaled approach using the NLSY79 - Canale, Anthony (Kansas State University, 2018)
Americans seem to be financially vulnerable and lack sufficient net worth to overcome financial obstacles such as unforeseen medical issues, temporary job loss, or changing economic conditions. Americans aren’t saving enough, have too much debt, and tend to have a short-sighted view on their finances. Wealth is a primary indicator of financial and economic security and maintaining and improving standard of living are two important financial goals. Aggregate net worth can be used to gauge the financial well-being of Americans because it includes both assets and liabilities. It is hypothesized that part of the instability which results in the lack of accumulating adequate wealth, is time preference. Time preference is an important psychological construct which examines the ability to defer gratification. Time preference represents the intertemporal choice between immediate versus delayed utility. A low rate of time preference implies a low rate of intertemporal discounting. Individuals with low discounting do not heavily discount the future and are able to defer gratification. A high rate of time preference or a high rate of intertemporal discounting, suggests that individuals are more present oriented, heavily discount the future, prefer immediate gratification. This research study takes a unique approach to examining time preference since the experimental community lacks a clear consensus on how to best measure this construct. Standard risk and time preferences measures are typically achieved through responses to financially incentivized choice questions. Researchers have argued that incentivized choice questions may be common but they lack precision. Therefore, combining behaviors that involve intertemporal tradeoffs into a scale to measure time preference is believed to be a more accurate indicator of time preference. However, there is little research that has reliably developed and tested its use. This research examines time preference by comparing incentive choice questions as a proxy for time preference as well as an additive scale of intertemporal behaviors using a national representative sample. Regression analysis revealed that that time preference measured using an additive scale of intertemporal behaviors was significantly associated with net worth. The incentive choice questions as a measure of time preference were not significantly associated with net worth. The respondents with a high rate of intertemporal discounting as measured by the time preference scale accumulated less net-worth than respondents with a lower rate of intertemporal discounting. In addition, in the regression model when individual behaviors involving intertemporal tradeoffs such as smoking, drinking, and not taking physical exams were added as individual behaviors, the model was the preferred predictor of net worth.
Keywords: Time preference; Net worth; Delay discounting; Time preference scale; Incentive choice